Engaging scientists through institutional histories - Shambu Prasad, C.; Hall, A.; Laxmi, T. (2006)
An institutional history is a narrative that records key points about how institutional arrangements – new ways of working – evolve over time creating more effective ways to achieve goals. It can be used to document institutional innovations in projects and to highlight barriers to change. An institutional history draws out and synthesizes lessons for research organizations and partners as well as for others in similar circumstances.